2015
DOI: 10.1002/star.201500012
|View full text |Cite
|
Sign up to set email alerts
|

Different types of V amylose–lipid inclusion complexes in maize extrudates revealed by DSC analysis

Abstract: Aqueous dispersions of the extrudates (1%) prepared from three maize varieties containing starches with the various amylose contents (20-53%) and the high lipid level (about 7% on dry starch weight) were studied by DSC analysis. Two different types of amylose-lipid complexes were observed in the direct process (20-120°C, peak temperature of about 105-107°C) and when reheating/rescanning modes were employed (peak temperature of about 85°C). The extrudate dispersions heated only up to 100°C in the direct DSC sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 11 publications
(34 reference statements)
0
18
0
Order By: Relevance
“…Similar in focus to the present study, lipid complexing has been researched by several groups using single or twin‐screw extruders . Reported studies have examined the influences of barrel temperature, screw speed, amylose source, and feed moisture in order to modify the extent of ALC formation . None have yet considered varying the extent of mixing inside the extruder as a means to control the reaction and RS fraction of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…Similar in focus to the present study, lipid complexing has been researched by several groups using single or twin‐screw extruders . Reported studies have examined the influences of barrel temperature, screw speed, amylose source, and feed moisture in order to modify the extent of ALC formation . None have yet considered varying the extent of mixing inside the extruder as a means to control the reaction and RS fraction of the final product.…”
Section: Introductionmentioning
confidence: 99%
“…The lipid droplets could also be incorporated into the lamella . Another possible reaction during extrusion cooking is the complex formation of lipids with amylose . However, these complexes can only be formed with free fatty acids or monoglycerides .…”
Section: Introductionmentioning
confidence: 99%
“…[6] Another possible reaction during extrusion cooking is the complex formation of lipids with amylose. [7][8][9] However, these complexes can only be formed with free fatty acids or monoglycerides. [10,11] The complex formation depends, among other things, on the kind of fat and the process parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Extrusion cooking of starch and lipids can form ALCs . Several authors have shown the occurrence of ALCs formation and found that the formation depends on the barrel temperature, moisture content, screw speed, and screw configuration. The optimal conditions for the formation of type I ALCs in the twin‐screw extrusion of starch with oleic acid addition were found to be a 128 °C barrel temperature with a barrel moisture content of 21% and a feed rate of 2.79 kg h −1 .…”
Section: Introductionmentioning
confidence: 99%
“…The optimal conditions for the formation of type I ALCs in the twin‐screw extrusion of starch with oleic acid addition were found to be a 128 °C barrel temperature with a barrel moisture content of 21% and a feed rate of 2.79 kg h −1 . Genkina et al reported that the occurrence of a type I ALCs with a single‐screw extruder varied with different amylose contents (20–53%) and a high internal lipid level (7% dry starch weight).…”
Section: Introductionmentioning
confidence: 99%